XEN Gel Stent to Treat Intraocular Hypertension After Dexamethasone-Implant Intravitreal Injections: 5 Cases. Issue 1 (January 2019) - Rezkallah, Amina; Mathis, Thibaud; Denis, Philippe; Kodjikian, Laurent
Abstract : Introduction: Intravitreal injections (IVI) of slow-release dexamethasone (DEX) are generally well tolerated. Ocular hypertension (OHT) and cataracts are the most common adverse effects of DEX-implant (DEX-I). Material and Methods: The cases reported concern 5 eyes in four DEX-I IVI high-responder patients whose intraocular pressure (IOP) returned to normal after administration of a XEN gel stent with mitomycin subconjunctival injection, thus allowing the continued use of DEX-I which was the only therapeutic option for these patients. All patients were pure steroid responders with normal optic nerves. Results: No hypertension was observed in any of the eyes after DEX-implant intravitreal reinjection following XEN-surgery. All patients were successfully treated with XEN surgery and were retreated with DEX-implant with no further increase in IOP. The mean duration of follow-up after the MIGS procedure was 5 months (min-max, 2-12). None of the patients required needling. Conclusions: XEN gel stent would seem to represent a safe and effective solution for treating steroid-induced hypertension. It allows for the medium and long-term use of DEX-I in high responders. It could be of clinical interest to study this combination in a prospective trial with a large number of patients and long-term follow-up.